Espaço Público: A Cidade em Cena - Laboratório Território e Cidadania da UFRJ (Espaço Aberto, 2011)
The documentary is a product of the experience of a group of geographers who observe public spaces that are a part of the dynamics which sustain and produce democratic societies.  A succession of common scenes from urban life in Rio de Janeiro are presented, which explore multi-focal possibilities and the cacophony of open spaces in large cities according to sociability, order and visibility.